Aspartate β-Hydroxylase (ASPH) Expression in Acute Myeloid Leukemia: A Potential Novel Therapeutic Target - Holtzman, Noa G.; Lebowitz, Michael S.; Koka, Rima; Baer, Maria R.; Malhotra, Kanam; Shahlaee, Amir; Ghanbari, Hossein A.; Bentzen, Søren M.; Emadi, Ashkan (Frontiers in Oncology, 2021)
Background: Aspartate β-hydroxylase (ASPH) is an embryonic transmembrane protein aberrantly upregulated in cancer cells, associated with malignant transformation and, in some reports, with poor clinical prognosis. Objective: To report the expression patterns of ASPH in acute myeloid leukemia (AML). Methods: Cell surface expression of ASPH was measured via 8-color multiparameter flow cytometry in 41 AML patient samples (31 bone marrow, 10 blood) using fluorescein isothiocyanate (FITC)-conjugated anti-ASPH antibody, SNS-622. A mean fluorescent intensity (MFI) of 10 was used as a cutoff for ASPH surface expression positivity. Data regarding patient and disease characteristics were collected. Results: ASPH surface expression was found on AML blasts in 16 samples (39%). Higher ASPH expression was seen in myeloblasts of African American patients (p=0.02), but no correlation was found between ASPH expression and other patient or disease characteristics. No association was found between ASPH status and CR rate (p = 0.53), EFS (p=0.87), or OS (p=0.17). Conclusions: ASPH is expressed on blasts in approximately 40% of AML cases, and may serve as a new therapeutically targetable leukemia-associated antigen.